Digital archives and collections : creating online access to cultural heritage - Müller, Katja (Anthropology of media, 2021)
"Museums and archives all over the world digitize their collections and provide online access to heritage material. But what factors determine the content, structure and use of these online inventories? This book turns to India and Europe to answer this question. It explains how museums and archives envision, decide and conduct digitization and online dissemination. It also sheds light on born-digital, community-based archives, which have established themselves as new actors in the field. Based on anthropological fieldwork, the chapters in the book trace digital archives from technical advancements and postcolonial initiatives to programming alternatives, editing content, and active use of digital archives"--